(untitled) (Res Medica, 2014)
‘My Chinese uncle, gouty, deaf, half-blinded, And more than a little absent-minded, Astonished all St. James’s Square one day By giving long and unexceptionally exact directions To a little coolie girl, who’d lost her way”. — Robert Graves. But what became of him later? If he had lived in Edinburgh his future would have been disturbingly bleak. At present the South-East Region has the least number of long-stay beds in Scotland. Care for the elderly has become one of the darkest betes-noires of the N .H.S., and, as far as expenditure goes, one with potentially the most voracious appetite.